Peran PT. Karya Dua Anyam dalam Mengelola Kerajinan Hasil Hutan Bukan Kayu Lontar (Borassus flabellifer Linn) terhadap Pemberdayaan Perempuan di Desa Wulublolong Kecamatan Solor Timur Kabupaten Flores Timur - Veronika Anna Lamen; I Nyoman W. Mahayasa; Nixon Rammang (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2022)
Non-Timber Forest products, which are usually abbreviated as NTFPs, are biological forest products and their derivative and cultivation products, except for wood originating from forests (Permenhut No. P.35/Menhut-II/2007 concerning Non-Timber Forest Products. NTFPs in East Nusa Tenggara Province have enormous potential enough to affect the lives of the surrounding community. One of the NTFPs is Lontar. Lontar is a plant that has a close relationship with the lives of the people of NTT because it can produce several types of products that are used as a main and additional source of income, especially handicrafts in the form of wicker that have been developed in Wulublolong Village, District East Solor, East Flores Regency under the guidance of PT. Karya Dua Anyam which is engaged in the field of Women's Empowerment. This study aims to determine the management of Lontar in Wulublolong Village and the role of PT. Karya Dua Anyam in helping the economy and socio-culture, especially women (mothers). PT. Karya Dua Anyam has contributed a lot to the progress of Wulublolong Village in terms of economic, social and cultural aspects. Many of the products that have been produced by weavers have a high selling value that can help their economy.